2018
DOI: 10.1021/acsami.8b07206
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Evolution of Piezoresponses and Stripe 90° Domains in (101)-Oriented Ferroelectric PbTiO3 Thin Films

Abstract: High-index ferroelectric films as (101)-orientated ones exhibit enhanced dielectric responses, piezoelectric responses, and exotic ferroelectric switching behaviors, which are potential candidates for applications in memories and capacitors. However, possible domain patterns and domain wall structures in (101)-oriented ferroelectric thin films are still elusive, which results in difficulties in understanding the origin and further modulating their special properties. In this work, a series of PbTiO (PTO) thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Thus, a PTO film of 50 nm was grown on a (101)-oriented (La,Sr)(Al,Ta)O3 (LSAT(101)) substrate and 90° DWs perpendicular to the film/substrate interface were found ( Supplementary Fig. 3), similar to our recent finding 15 . In this orientation, the two domains beside a 90° DW are in symmetric strain states, so that most 90° DWs are very straight.…”
supporting
confidence: 86%
“…Thus, a PTO film of 50 nm was grown on a (101)-oriented (La,Sr)(Al,Ta)O3 (LSAT(101)) substrate and 90° DWs perpendicular to the film/substrate interface were found ( Supplementary Fig. 3), similar to our recent finding 15 . In this orientation, the two domains beside a 90° DW are in symmetric strain states, so that most 90° DWs are very straight.…”
supporting
confidence: 86%
“…At room temperature, PTO is a typical tetragonal ferroelectrics with lattice parameters of a = b = 3.899 Å and c = 4.153 Å, whereas STO exhibits a cubic structure with lattice parameters of a = b = c = 3.905 Å. In contrast to the (001) orientation, STO(101) substrates have two different in-plane crystal axes, [010] and [1̅01], which bring asymmetric biaxial strain for PTO thin films. , The surface topographies of [001]­PTO and [101]­PTO thin films are shown in Figure a,b, respectively. From Figure a, it is seen that the [001]­PTO thin film exhibits a very smooth surface with the surface root-mean-square (rms) roughness of 152 pm.…”
Section: Results and Discussionmentioning
confidence: 99%
“…So far, most studies on polarization rotation have focused on (001)-oriented films. However, recent studies have revealed that the crystallographic orientation of ferroelectric films has a great effect on the domain configuration, , dielectric property, and ferroelectric switching behavior . Furthermore, theoretically, the temperature-strain phase diagrams of single domain (101)-oriented PTO thin films indicated that the PTO films grown on SrTiO 3 (STO) substrates could be a monoclinic a 2 c phase or an orthorhombic c phase, which means that the polarization rotation may exist in PTO/STO(101) films due to the monoclinic–orthorhombic ferroelectric morphotropic phase boundary…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, these growth defects generally have a negative impact on the properties of ferroelectric films. 10,11 For instance, it is noticeable that the presence of impurity defects will affect the performance of oxide films prepared by PLD. It has been demonstrated that local phase separation is a general reason for fatigue in ferroelectric films.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, defects may be involved in ferroelectric thin films if the growth conditions, such as oxygen partial pressure, substrate temperature, and annealing rate, are not manipulated accurately . Moreover, these growth defects generally have a negative impact on the properties of ferroelectric films. , For instance, it is noticeable that the presence of impurity defects will affect the performance of oxide films prepared by PLD. It has been demonstrated that local phase separation is a general reason for fatigue in ferroelectric films.…”
Section: Introductionmentioning
confidence: 99%